O-GlcNAcylation in Hyperglycemic Pregnancies: Impact on Placental Function - Ning, Jie; Yang, Huixia (Frontiers in Endocrinology, 2021)
The dynamic cycling of N-acetylglucosamine, termed as O-GlcNAcylation, is a post-translational modification of proteins and is involved in the regulation of fundamental cellular processes. It is controlled by two essential enzymes, O-GlcNAc transferase and O-GlcNAcase. O-GlcNAcylation serves as a modulator in placental tissue; furthermore, increased levels of protein O-GlcNAcylation have been observed in women with hyperglycemia during pregnancy, which may affect the short-and long-term development of offspring. In this review, we focus on the impact of O-GlcNAcylation on placental functions in hyperglycemia-associated pregnancies. We discuss the following topics: effect of O-GlcNAcylation on placental development and its association with hyperglycemia; maternal-fetal nutrition transport, particularly glucose transport, via the mammalian target of rapamycin and AMP-activated protein kinase pathways; and the two-sided regulatory effect of O-GlcNAcylation on inflammation. As O-GlcNAcylation in the placental tissues of pregnant women with hyperglycemia influences near- and long-term development of offspring, research in this field has significant therapeutic relevance.